Model Pembelajaran Guided Teaching untuk Meningkatkan Partisipasi Belajar dan Hasil Belajar IPS Siswa Kelas VI - Anizar Anizar (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2016)
The lack of participation in learning Social subject of the sixth grade students at SDN 27 Lubuk Alung gave effect on their low learning achievement. This research was aimed to improve the participation in learning and learning achievement of the sixth grade students at SDN 27 Lubuk Alung by implementing the Guided Teaching learning model. Kind of participations concerned with are participation in proposing ideas, participation in answering the teachers’ questions, and participation in asking questions to teacher. Data of research were obtained through observation and post test and were analyzed quantitatively and qualitatively. In cycle I, percentage of students’ participation in proposing ideas is 34,37% and becomes 78,12% in cycle II. Percentage of students’ participation in answering teachers’ questions is 37,49% in cycle I and becomes 81,25% in cycle II. Percentage of students’ participation in asking questions to teacher is 26,16% in cycle I and becomes 75% in cycle II. In cycle I, percentage of students’ learning achievement is 46,87℅ and becomes 87,5℅ in cycle II. The result shows that implementation of Guided Teaching model can improve participation in learning and learning achievement.